Development of Mathematics Learning Media Using Kvisoft Flipbook Application for Linear Programming Material - Resdiana Safithri (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This research aims to produce valid and practical mathematics learning media using the Kvisoft flipbook application for linear programming material, and to evaluate its potential effect on student learning outcomes. This study employed the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques included observation, interviews, validation sheets, questionnaires, and a test consisting of 5 post-test questions. The validity test was conducted by material experts, media experts, language experts, as well as a material expert assessment of the post-test questions. The subjects of this study were 24 students from class XI 5 of SMA N 5 Jambi City. The small group product trial was conducted at the implementation stage with 10 students from class XI 2, while the large group trial was conducted on 24 students from class XI 4. The assessment results showed a percentage of 95.3% for material with a "very valid" category, 96% for media with a "very valid" category, and 96% for language with a "very valid" category. For practicality, the percentage obtained was 97% with a "very practical" category by the subject educator. In the small group trial stage, the Kvisoft flipbook learning media for linear programming material obtained a percentage of 97.69% with a "very practical" category, and in the large group trial stage, the practicality questionnaire percentage was 95.51% with a "very practical" category. For effectiveness, the percentage obtained was 87.50% with a "very effective" category. Based on the analysis results of the validator questionnaires, student and teacher responses, it can be concluded that the Kvisoft flipbook learning media for linear programming material for class XI is valid, practical, and has a potential effect on student learning outcomes.